2022
DOI: 10.1016/j.dcn.2022.101069
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of cortical beta bursts in developmental EEG data

Abstract: Developmental EEG research often involves analyzing signals within various frequency bands, based on the assumption that these signals represent oscillatory neural activity. However, growing evidence suggests that certain frequency bands are dominated by transient burst events in single trials rather than sustained oscillations. This is especially true for the beta band, with adult ‘beta burst’ timing a better predictor of motor behavior than slow changes in average beta amplitude. No developmental research th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 85 publications
(143 reference statements)
3
20
0
Order By: Relevance
“…Studies of sensorimotor activity in developing populations typically focus on the alpha or mu frequency bands, and little is known about the development of beta band activity in infancy (Cuevas et al, 2014; Perone & Gartstein, 2019). It has recently been shown that, similar to alpha, there are age-related changes in beta frequency and power (He et al, 2019; Johnson et al, 2019; Rayson et al, 2022; Trevarrow et al, 2019) from infancy to adulthood. In infancy, the peak beta frequency is 15 Hz (Rayson et al, 2022), but movement-related artifacts from facial and arm movements also occur around this frequency (Georgieva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of sensorimotor activity in developing populations typically focus on the alpha or mu frequency bands, and little is known about the development of beta band activity in infancy (Cuevas et al, 2014; Perone & Gartstein, 2019). It has recently been shown that, similar to alpha, there are age-related changes in beta frequency and power (He et al, 2019; Johnson et al, 2019; Rayson et al, 2022; Trevarrow et al, 2019) from infancy to adulthood. In infancy, the peak beta frequency is 15 Hz (Rayson et al, 2022), but movement-related artifacts from facial and arm movements also occur around this frequency (Georgieva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that, similar to alpha, there are age-related changes in beta frequency and power (He et al, 2019; Johnson et al, 2019; Rayson et al, 2022; Trevarrow et al, 2019) from infancy to adulthood. In infancy, the peak beta frequency is 15 Hz (Rayson et al, 2022), but movement-related artifacts from facial and arm movements also occur around this frequency (Georgieva et al, 2020). This makes it extremely difficult to separate movement-related neural activity from artifactual activity using TF-based analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, especially in infancy, oscillatory brain activity appears in bursts, and is not constant across the entire register (Jones, 2016). Therefore, testing the appearance of those bursts and computing the power with them would probably increase the reliability of results and give other parameters of interest (Cole & Voytek, 2019; Ostlun et al, 2022; Rayson, et al, 2022). Finally, as infants protocols incorporate an active baseline, registering peripheral and behavior measures related to infants’ cognitive state could give us information and increase the comparability between infant and other developmental studies (Orekhova, Stroganova, & Posikera, 2001; Xie, Mallin, & Richards, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, identification of harmonics via the instantaneous frequency has been put forward (Fabus et al, 2022). The distinction between harmonic and genuine beta bursts is especially of interest for analyses performed in sensor space, as often done in developmental data (Rayson et al, 2022). If a rhythm is attributed to a harmonic, it may be beneficial to continue the analysis using the underlying base-frequency band instead of the harmonic frequency-band for further analyses, in order to profit from a much higher signal-to-noise ratio of the base frequency rhythm.…”
Section: Practical Recommendationsmentioning
confidence: 99%